2005
DOI: 10.1074/jbc.m500917200
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gene Expression Differentially Regulated by Platelet-derived Growth Factor and Hypertrophic Stimuli in Vascular Smooth Muscle Cells

Abstract: In vascular smooth muscle cells (VSMC), platelet-derived growth factor (PDGF) suppresses expression of multiple smooth muscle contractile proteins, useful markers of differentiation. Conversely, hypertrophic agents induce expression of these genes. The goal of this study was to employ genomic approaches to identify classes of genes differentially regulated by PDGF and hypertrophic stimuli. Changes in gene expression were determined using Affymetrix RAE-230 GeneChips in rat aortic VSMC stimulated with PDGF. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Based on the gene array analysis, 30 PDGF-BB increased the mRNA expression of a condroidin sulfate proteoglycan, Versican, and a cytokine, Gro, but decreased the expression of Collagen X 1␣. Quantitative Real-Time PCR (Q-RT-PCR) analysis showed that VSMC depleted of SRF (SRF shRNAi Clones #2, and #6) also had marked increases in mRNA levels for Versican when compared with control cells (U6.1/ Neo clones #1 and #2).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the gene array analysis, 30 PDGF-BB increased the mRNA expression of a condroidin sulfate proteoglycan, Versican, and a cytokine, Gro, but decreased the expression of Collagen X 1␣. Quantitative Real-Time PCR (Q-RT-PCR) analysis showed that VSMC depleted of SRF (SRF shRNAi Clones #2, and #6) also had marked increases in mRNA levels for Versican when compared with control cells (U6.1/ Neo clones #1 and #2).…”
Section: Resultsmentioning
confidence: 99%
“…During injury to blood vessels, PDGF triggers phenotypic modulation, which is mediated by changes in patterns of gene expression. Recently, a subset of genes has been defined that are up-or down-regulated in VSMC by PDGF (Kaplan-Albuquerque et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The induction of PDGFB mRNA and the expression of many of its first degree interacting nodes, is consistent with PDGFB signaling being upregulated by NKX3.1. For example, three nodes that were upregulated by NKX3.1 (CRYAB, SERPINA3, CDKN1A) and two nodes that were downregulated (DAB2, TAGLN) were previously shown to be controlled by PDGFB in the same manner ( Supplementary Figure S4; 80, 81 ). PDGFB is also known to activate PPAR/RXRα-dependent transcription.…”
Section: Resultsmentioning
confidence: 96%